A Cell-free Protein Synthesis Method for the Detection of Heavy Metal Ions Using a Personal Glucose Meter - Lee, Ju-Hui; Song, Dong-Yeon; Lim, Hye Jin; Kim, Dong-Myung (Biotechnology and bioprocess engineering, 2023)
Heavy metal pollution of water can pose a serious threat to public health. Because pollution can occur at multiple stages of water distribution, portable on-site detection methods are highly desirable for routine monitoring of water contamination. Here, we developed a method that enables the detection of heavy metal ions using a personal glucose meter (PGM), a readily accessible analytical device. The method utilizes a cell-free genetic circuit that generates glucose in response to heavy metal ions. The cell-free protein synthesis reaction mixture includes template DNA encoding the invertase enzyme under the control of operators for heavy metal-responsive transcription factors. When supplied with heavy metal ions cognate to the transcription factors, the reaction mixture successfully generated functional invertase, which subsequently hydrolyzed sucrose to glucose. The resulting glucose levels measured using a PGM correlated well with the concentrations of the heavy metal ions, supporting the feasibility of this method to detect water pollution without sophisticated equipment. Our results demonstrate a successful example of harnessing cell-free protein synthesis to transform analytes into surrogate molecules that can be readily measured with generic analytical devices. We expect that the method described here could be adapted for widespread application in numerous fields in which routine monitoring of analytes is required.